2013
DOI: 10.1038/labinvest.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo evaluation of antifibrotic compounds in skin scarring: EGCG and silencing of PAI-1 independently inhibit growth and induce keloid shrinkage

Abstract: Keloid disease (KD) is a common fibroproliferative disorder of unknown etiopathogenesis. Its unique occurrence in human skin and lack of animal models pose challenges for KD research. The lack of a suitable model in KD and overreliance on cell culture has hampered the progress in developing new treatments. Therefore, we evaluated the effect of two promising candidate antifibrotic therapies: ( À )-epigallocatechin-3-gallate (EGCG) and plasminogen activator inhibitor-1 (PAI-1) silencing in a long-term human kelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 28 publications
(51 reference statements)
4
57
0
Order By: Relevance
“…Finally, the effects of therapies on the whole skin or scar can be studied by obtaining a biopsy for ex vivo organ culture. 7780 The major advantage of this type of culture is that all of the cell types that participate in wound healing and scarring are present, allowing better elucidation of the mechanics of healing when compared to in vitro studies utilizing a single cell type, such as fibroblasts. These models can be used to study how to modulate the healing process to mimic that seen in tissues which do not scar.…”
Section: Models For Studying Post-burn Scarmentioning
confidence: 99%
“…Finally, the effects of therapies on the whole skin or scar can be studied by obtaining a biopsy for ex vivo organ culture. 7780 The major advantage of this type of culture is that all of the cell types that participate in wound healing and scarring are present, allowing better elucidation of the mechanics of healing when compared to in vitro studies utilizing a single cell type, such as fibroblasts. These models can be used to study how to modulate the healing process to mimic that seen in tissues which do not scar.…”
Section: Models For Studying Post-burn Scarmentioning
confidence: 99%
“…This finding support the hypothesis proposed by Leppert et al and may help enhance the understanding of keloid pathogenesis. Based on our preliminary findings, future investigations are warranted to determine the effects of gonadotropin-releasing hormone (Gn-RH) agonists on keloids in female patients with leiomyomata, and evaluate the ex vivo effects of Gn-RH agonists or progestins in keloid organ cultures [41].…”
Section: Comorbid Diseasesmentioning
confidence: 99%
“…This model has several advantages; the keloid explants remain viable in culture for up to 6 weeks without tissue deterioration, the maintenance of the keloid cellular and microenvironments enable examination of keloid pathophysiology in situ and anti‐fibrotic agents and gene silencing using RNA interference technology can be used to investigate the cellular and molecular interactions in the epidermis and dermis . The results showed that these therapies inhibited growth and induced shrinkage of human keloid tissue and found this to be an effective model . Another study assessed the extent to which differences relating to cell type influence PAI‐1 gene regulation with regard to growth state‐associated mechanisms of expression control using keloid fibroblasts and normal dermal fibroblasts for cell culture …”
Section: Resultsmentioning
confidence: 99%